Bronchopulmonary Dysplasia in Premature Infants: Pathogenesis, Clinical Picture, Treatment and Prevention (Part 1) - V.I. Snysar; O.I. Obolonsky; D.M. Surkov; O.G. Kapustina; D.G. Volkov (Zaslavsky O.Yu., 2013)
The article describes the current views on the pathogenesis, clinical picture, diagnosis and treatment of bronchopulmonary dysplasia. Special attention is paid to the influence of ductus arteriosus on the occurrence and severity of bronchopulmonary dysplasia, to the mechanisms of the hemodynamic effects of patent ductus arteriosus on blood flow in the anterior cerebral artery, the vessels of the pulmonary circulation, the impact of patent duct on the development of pulmonary edema. Separately, the methods for closure of patent ductus arteriosus were considered. The advantages of pharmacologic ductal closure are noted.